RESPON PERTUMBUHAN Acartia sp. TERHADAP PENERAPAN KUNING TELUR, PELET DAN YEAST SEBAGAI SUMBER NUTRISI - Muliani Muliani; Fahrezza Fahrezza; Rachmawati Rusydi; Eva Ayuzar; Salamah Salamah (Journal of Fish Nutrition, 2021)
Acartia sp is a zooplankton that has the potential to be developed and used as naturalfeed for marine fish larvae. The problem in cultivation is that the right feed is neededas a support for the growth of Acartia sp so that maximum production and feed needsfrom larvae are fulfilled. This study aims to find out the growth response of Acartia sp to the application of egg yolks, pellets and yeast as a source of nutrition. Researchparameters include abundance levels, population peaks, growth rates and waterquality on Acartia sp maintenance. The research method is an experimental laboratorywith 4 (four) treatment levels and 3 (three) repeats. The treatment standards are A:Pellets, B:Egg yolks, C: Yeast (yeast), and D: Nannochloropsis sp (control). Theresearch phase consists of preparation of Acartia sp feed (egg yolk, pellet, yeast, andNannochloropsis sp), feeding, and maintenance of Acartia sp. The results showed thatacculturation of Acartia sp with feed differences affected daily abundance, populationpeak, and growth rate of Acartia sp with the best treatment indicated byNannocloropsis sp (control). The peak population of Acartia sp reached 633.33 ind /L, the growth rate of Acartia sp reached 106.6 ind / day. However, the provision ofpellets becomes an alternative to Acartia sp feed that has the potential to support itsgrowth. The value of water quality parameters during the study is still optimal, namelytemperature 25-27 °C, salinity 33-35 ppt, pH 7.1-7.9, DO 4.9-6.6 mg / L, and ammonia0.087-0.284 ppm.